Investigating the role of tumour cell derived iNOS on tumour growth and vasculature in vivo using a tetracycline regulated expression system. Issue 11 (8th February 2016) - Papaevangelou, Efthymia; Whitley, Guy S.; Johnstone, Alan P.; Robinson, Simon P.; Howe, Franklyn A.
Abstract : Nitric oxide (NO) is a free radical signalling molecule involved in various physiological and pathological processes, including cancer. Both tumouricidal and tumour promoting effects have been attributed to NO, making its role in cancer biology controversial and unclear. To investigate the specific role of tumour‐derived NO in vascular development, C6 glioma cells were genetically modified to include a doxycycline regulated gene expression system that controls the expression of an antisense RNA to inducible nitric oxide synthase (iNOS) to manipulate endogenous iNOS expression. Xenografts of these cells were propagated in the presence or absence of doxycycline. Susceptibility magnetic resonance imaging (MRI), initially with a carbogen (95% O2 /5% CO2 ) breathing challenge and subsequently an intravascular blood pool contrast agent, was used to assess haemodynamic vasculature (Δ R 2 *) and fractional blood volume (fBV), and correlated with histopathological assessment of tumour vascular density, maturation and function. Inhibition of NO production in C6 gliomas led to significant growth delay and inhibition of vessel maturation. Parametric fBV maps were used to identify vascularised regions from which the carbogen‐induced Δ R 2 * was measured and found to be positively correlated with vessel maturation, quantified ex vivo using fluorescence microscopy for endothelial and perivascular cell staining. These data suggest that tumour‐derived iNOS is an important mediator of tumour growth and vessel maturation, hence a promising target for anti‐vascular cancer therapies. The combination of Δ R 2 * response to carbogen and fBV MRI can provide a marker of tumour vessel maturation that could be applied to non‐invasively monitor treatment response to iNOS inhibitors. Abstract : What's new? Another party weighs in on the controversial subject of nitric oxide. Does it boost tumour growth or hinder it? These authors observed that nitric oxide promoted vascular maturation and boosted tumour growth in glioma cells. They engineered a new system that allowed them to induce the cells' own production of nitric oxide synthase and measure the effect of tumour‐derived nitric oxide on growth. When they suppressed production of nitric oxide, tumour growth slowed. In addition, they successfully used susceptibility MRI to non‐invasively visualise tumour vasculature, highlighting the usefulness of this tool in monitoring vascular maturation in response to treatment.